Long-acting anti-aging aerogel, polyurethane composition containing same, and preparation method and application of polyurethane foam
By using long-lasting aging-resistant airgel in polyurethane materials, the problem of performance degradation of polyurethane materials during the aging process is solved, the long-lasting resistance to heat and oxygen aging and light aging resistance of the material are improved, and maintenance costs are reduced.
Patent Information
- Application Number
- CN202410002491.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-02
- Publication Date
- 2025-01-21
AI Technical Summary
After long-term aging of existing polyurethane materials, the consumption of antioxidants and light stabilizers leads to a decline in material performance, increasing the frequency and cost of maintenance.
A long-lasting aging-resistant aerogel is used, which is prepared from alcohol gel and a composite anti-aging agent. It is used in the polyurethane composition to improve the foaming efficiency and stability, and achieve the slow-release effect of antioxidants and light stabilizers.
It significantly reduces the dosage of antioxidants and light stabilizers, reduces raw materials and construction and maintenance costs, and improves the long-term heat and oxygen aging resistance and light aging resistance of polyurethane foam.
Smart Images

Figure BDA0004644607910000151 
Figure BDA0004644607910000161 
Figure BDA0004644607910000171
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyurethane materials, and in particular to a long-lasting anti-aging aerogel, a polyurethane composition containing the aerogel, and a preparation method and application of polyurethane foam. Background Art
[0002] Ballasted track is a traditional railway track, usually composed of two parallel rails fixed on sleepers, with ballast made of small gravel underneath. Ballast and sleepers play the role of increasing the load-bearing surface, dispersing the pressure of the train, and helping the rails to bear the weight, in order to prevent the rails from sinking into the soil due to excessive pressure. Traditional ballasted track has the characteristics of easy laying and low overall cost, but it is easy to deform, requires frequent maintenance, and has high maintenance costs. In addition, the graded ballast of existing railways has already deteriorated, and these conditions are more obvious under the current conditions of frequent transportation and large loads. At present, many countries and regions are increasing their research efforts in this regard, trying to find effective ways to reduce the maintenance of existing railways, extend their service life, and thus reduce operating costs.
[0003] Polyurethane solidified ballast bed is to pour polyurethane material into the gravel ballast bed that has reached a stable state, complete foaming, expansion and solidification between the ballasts, so that the polyurethane material fills the gaps between the ballasts and firmly bonds the ballast particles to form an elastic consolidated integral ballast bed structure. Its good mechanical properties make this technical solution take into account the good elasticity of ballasted track and the stability of ballastless track structure.
[0004] Due to its excellent comprehensive performance, polyurethane cured ballast bed technology has become a recommended solution for laying railway lines in some key sections, especially in areas with complex road conditions such as high altitude drop, high bridge-tunnel ratio, plate activity, mountain disasters, etc. The current level of polyurethane cured ballast bed formulation enables the ballast bed to exhibit good aging resistance and light aging resistance in the early stage of molding. However, with the increase of aging time, the consumption of antioxidants and light stabilizers, the performance of the polyurethane body, especially the surface layer, will decline, resulting in a decline in the overall performance of the ballast bed, which in turn affects the track stability and driving safety. At this time, local maintenance of the polyurethane material is necessary, and the increase in raw material costs, construction and maintenance costs, etc. will inevitably lead to an increase in the overall cost.
[0005] At present, in order to further improve the performance of roadbed materials, especially the heat-oxidative aging and light-aging resistance of the surface layer to reduce the construction and maintenance costs, the technical solution in the industry is to add more antioxidants and light stabilizers, which brings some disadvantages: 1) the cost of raw materials increases significantly; 2) the storage stability deteriorates, and the production process becomes difficult; 3) the performance of the PU foam itself is greatly affected. Therefore, the current solution is not an effective solution for the long-term development of the industry.
[0006] CN105237699A discloses a polyurethane soft foam material for a solidified roadbed and a preparation method thereof, and discloses a polyurethane foam material for a solidified roadbed and a polyurethane foam material having a density of ≤350kg / m 3 The foam performance in the molded samples, including the aging resistance in the initial stage of molding, cannot solve the pain point of long-term aging resistance in the industry.
[0007] CN112920377A discloses a polyurethane soft foam material for a solidified roadbed and a preparation method thereof, wherein a prefabricated process is used to prepare a polyurethane solidified roadbed, and a density of 285 kg / m 3 The foam performance in the molded samples, including the aging resistance in the initial stage of molding, still cannot solve the pain point of long-term aging resistance in the industry.
[0008] Therefore, it is necessary to provide a technical solution to further improve the long-term heat and oxygen aging resistance, light aging resistance and other properties of polyurethane materials to reduce the frequency of maintenance, while not causing a significant increase in raw material costs, and to ensure that the construction process is convenient and reliable, so as to have faster development and broader prospects in the railway industry. Summary of the invention
[0009] In order to solve the problems existing in the prior art, the present invention provides a long-lasting aging-resistant aerogel, which can be used in a polyurethane composition, has very good storage stability and process convenience, can improve the foaming efficiency and stability during the foaming process, and can also achieve the sustained release effect of antioxidants and light stabilizers, thereby greatly reducing the dosage of antioxidants and light stabilizers, and significantly reducing raw material costs and construction and maintenance costs.
[0010] Another object of the present invention is to provide a method for preparing the long-lasting aging-resistant aerogel.
[0011] Another object of the present invention is to provide a polyurethane composition containing long-lasting aging-resistant aerogel, which can be used for the preparation of polyurethane foam, especially the preparation and application of polyurethane foam for cured roadbed, and has low cost, convenient process, excellent mechanical properties and very excellent long-term resistance to heat and oxygen aging and light aging.
[0012] To achieve the above invention objectives, the technical solutions of the present invention are as follows:
[0013] A long-lasting anti-aging aerogel is prepared from alcohol gel and a composite anti-aging agent.
[0014] In some specific embodiments, the composite anti-aging agent consists of an antioxidant and a light stabilizer;
[0015] In some preferred embodiments, the composite antioxidant is composed of 60-70wt% antioxidant and 30-40wt% light stabilizer; for example, the composite antioxidant is composed of 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt% antioxidant and 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt% light stabilizer.
[0016] In some preferred embodiments, the antioxidant is selected from one or more of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid isooctyl ester, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid branched C7-C9 carbon alkyl ester, PUR70, and PU68F;
[0017] The light stabilizer is selected from one or more of 2-(2'-hydroxy-3'-dodecyl-5'-methylphenyl)benzotriazole, the reaction product of 3-[3-(2H-benzotriazolyl-2)-5-tert-butyl-4-hydroxyphenyl]malonate and polyethylene oxide, and bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate.
[0018] On the other hand, the method for preparing the long-lasting aging-resistant aerogel comprises the following steps:
[0019] 1) suspending calcium oxide in anhydrous methanol, heating and stirring, bubbling carbon dioxide through a reactor until all the calcium oxide is dissolved and converted into an alcohol gel, stopping the introduction of carbon dioxide, and allowing the reaction to stand to obtain an alcohol gel;
[0020] 2) placing the alcohol gel in an autoclave, and adding an anhydrous methanol solution of a composite anti-aging agent until the gel is just completely immersed in the solution;
[0021] 3) Seal the autoclave, slowly pressurize it with carbon dioxide to not less than 6.0 MPa, preferably 6.0-6.5 MPa, control the temperature in the autoclave to 281-292 K, maintain for 4-6 hours, then reduce the pressure to 4.0-4.5 MPa, and then pressurize it with carbon dioxide to not less than 6.0 MPa, for example 6.5 MPa;
[0022] 4) Repeat step 3) 3 to 5 times; then, heat the autoclave to a temperature higher than the critical temperature of carbon dioxide, preferably greater than or equal to 316K, and maintain for 1 to 3 hours;
[0023] 5) Slowly reducing the pressure to atmospheric pressure to obtain the long-lasting aging-resistant aerogel.
[0024] In some specific embodiments, the heating and stirring in step 1) is performed at a temperature of 40 to 50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, etc., for a time of 90 to 120 min, for example, 90 min, 95 min, 100 min, 105 min, 110 min, 115 min, 120 min, etc., the carbon dioxide flow rate is 1 to 2 L / min, for example, 1.5 L / min, the bubbling time is 1 to 2 h, for example, 1.5 h, and the standing time is 0.5 to 1 h, for example, 0.8 h.
[0025] In some specific embodiments, the weight ratio of calcium oxide to anhydrous methanol in step 1) is 1:20 to 1.5:20, for example, 1:20, 1.1:20, 1.2:20, 1.3:20, 1.4:20, 1.5:20, etc.
[0026] In some specific embodiments, the weight ratio of the composite anti-aging agent to anhydrous methanol in step 2) is 1:1 to 1:1.5, for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, etc.
[0027] In another aspect of the present invention, a polyurethane composition is obtained by reacting an isocyanate component and an isocyanate-reactive component, wherein the isocyanate-reactive component comprises: polyether polyol 1, polyether polyol 2, polymer polyol, foaming agent, flame retardant, chain extender, crosslinking agent, surfactant, catalyst, and long-lasting aging-resistant aerogel; wherein the long-lasting aging-resistant aerogel is prepared by the aforementioned method or the aforementioned long-lasting aging-resistant aerogel.
[0028] In some specific embodiments, the polyether polyol 1 has an average functionality of 2 to 4.5, such as 2, 2.5, 3, 3.5, 4, 4.5, etc., preferably 3, a hydroxyl value of 10 to 200 mgKOH / g, such as 10 mgKOH / g, 15 mgKOH / g, 20 mgKOH / g, 25 mgKOH / g, 30 mgKOH / g, 35 mgKOH / g, 40 mgKOH / g, 50 mgKOH / g, 60 mgKOH / g, 70 mgKOH / g, 80 mgKOH / g, 90 mgKOH / g, 100 mgKOH / g, 130 mgKOH / g, 150 mgKOH / g, 180 mgKOH / g, 200 mgKOH / g, etc., preferably 20 to 40 mgKOH / g, and is composed of a cyclic The polyether polyol 1 is obtained by reacting ethylene oxide and propylene oxide, wherein the content of ethylene oxide is 10-25wt%, for example, 10wt%, 15wt%, 20wt%, 25wt%, etc., based on the total mass of propylene oxide and ethylene oxide as 100%; the polyether polyol 1 is, for example, a class of compounds initiated by polyols and polymerized by alkylene oxides, and examples of initiators include but are not limited to ethylene glycol, propylene glycol, 1,4-butanediol, dipropylene glycol, diethylene glycol, triethylene glycol, bisphenol A, glycerol, trimethylolpropane, diethanolamine, triethanolamine, ethylenediamine, toluene diamine, pentaerythritol, sorbitol, xylitol, sucrose or a mixture thereof, and the alkylene oxide monomer can be block addition or random addition, preferably block addition, and further preferably propylene oxide polymerization, and ethylene oxide block addition is performed at the end.
[0029] In some specific embodiments, the polyether polyol 2 has an average functionality of 2 to 3, such as 2, 2.5, 3, etc., preferably 2, and a hydroxyl value of 10 to 200 mgKOH / g, such as 10 mgKOH / g, 15 mgKOH / g, 20 mgKOH / g, 25 mgKOH / g, 30 mgKOH / g, 35 mgKOH / g, 40 mgKOH / g, 50 mgKOH / g, 60 mgKOH / g, 70 mgKOH / g, 80 mgKOH / g, 90 mgKOH / g, 100 mgKOH / g, 130 mgKOH / g, 150 mgKOH / g, 180 mgKOH / g, 200 mgKOH / g, etc., preferably 20 to 40 mgKOH / g. gKOH / g, obtained by the reaction of ethylene oxide and propylene oxide, the ethylene oxide content is 5-10wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc., based on the total mass of propylene oxide and ethylene oxide as 100%; the polyether polyol 2 is, for example, a class of compounds initiated by polyols and polymerized by alkylene oxides, examples of initiators include but are not limited to ethylene glycol, propylene glycol, 1,4-butanediol, dipropylene glycol, diethylene glycol, triethylene glycol, bisphenol A, glycerol, trimethylolpropane, diethanolamine, triethanolamine, ethylenediamine, toluenediamine, pentaerythritol or a mixture thereof, and the alkylene oxide monomer can be block addition or random addition, preferably random addition.
[0030] In some specific embodiments, the polymer polyol, i.e., graft copolymer polyether polyol, has an average functionality of 2 to 4.5, for example, 2, 2.5, 3, 3.5, 4, 4.5, etc., preferably 3, a hydroxyl value of 15 to 50 mgKOH / g, for example, 15 mgKOH / g, 20 mgKOH / g, 25 mgKOH / g, 30 mgKOH / g, 35 mgKOH / g, 40 mgKOH / g, 45 mgKOH / g, 50 mgKOH / g, etc., preferably 20 to 40 mgKOH / g, and a solid content of 20 to 50 wt%, for example, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, etc., preferably 25 to 45 wt%. Specifically, the polymer polyol is a type of graft copolymer polyol obtained by reacting a polyether polyol and a vinyl monomer, wherein the polyether polyol can be polyoxyethylene polyol, polyoxypropylene polyol, polyoxyethylene-oxypropylene copolymer polyol, etc. commonly used in the art, and the vinyl monomer can be acrylonitrile, styrene, vinylidene chloride, hydroxyalkyl acrylate and alkyl acrylate, etc., preferably acrylonitrile and / or styrene.
[0031] In some specific embodiments, the NCO content of the isocyanate component is 10 to 32%, for example, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, etc., preferably 17 to 20%, and the viscosity at 25°C is 100 to 1000mpa·s, for example, 100mpa·s, 200mpa·s, 300mpa·s, 400mpa·s, 500mpa·s, 600mpa·s, 700mpa·s, 800mpa·s, 900mpa·s, 1000mpa·s, etc., preferably 300 to 800mpa·s. Specifically, the isocyanate component refers to a class of compounds having an isocyanate group, examples of which include but are not limited to toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), dicyclohexylmethane diisocyanate (HMDI), naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), 1,4-cyclohexane diisocyanate (CHDI), xylene diisocyanate (XDI), cyclohexane dimethylene diisocyanate (HXDI), trimethyl-1,6-hexamethylene diisocyanate (TMHDI), tetramethyl meta-xylene diisocyanate (TMXDI), norbornane diisocyanate (NBDI), dimethyl biphenyl diisocyanate (TODI), methylcyclohexyl diisocyanate (HTDI), etc., as well as prepolymers, modified products, polymers, etc. of such monomers. Such isocyanate compounds can be used alone or in combination.
[0032] In some specific embodiments, the molar ratio of isocyanate groups in the isocyanate component to active hydrogen atoms in the isocyanate reactive component is 80-120:100, for example, 80:100, 85:100, 90:100, 95:100, 100:100, 105:100, 110:100, 120:100, etc., preferably 95-105:100.
[0033] The polyurethane composition comprising the polyether polyol 1, the polyether polyol 2, the polymer polyol, the foaming agent, the flame retardant, the chain extender, the crosslinking agent, the surfactant, the catalyst, the long-lasting aging-resistant aerogel and the isocyanate component is used for preparing polyurethane foam, has low cost, convenient process, excellent mechanical properties and very excellent long-term resistance to heat and oxygen aging and light aging, and can be used for large-scale production of polyurethane cured roadbeds.
[0034] In some specific embodiments, based on the total mass of the isocyanate reactive component, the isocyanate reactive component comprises:
[0035] The amount of polyether polyol 1 is 30-60%, for example, 30%, 33%, 35%, 37%, 40%, 41%, 43%, 45%, 46%, 48%, 50%, 55%, 60%, etc.;
[0036] The amount of polyether polyol 2 is 20-50%, for example, 20%, 21%, 22%, 23%, 24%, 25%, 28%, 30%, 33%, 35%, 37%, 40%, 41%, 43%, 45%, 46%, 48%, 50%;
[0037] The amount of polymer polyol is 5-15%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.;
[0038] The amount of foaming agent is 0.7-1.5%, for example, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.5%, etc.;
[0039] The amount of flame retardant is 5-20%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.;
[0040] The amount of chain extender is 1-5%, for example, 1%, 2%, 3%, 4%, 5%, etc.;
[0041] The amount of the crosslinking agent is 1-5%, for example, 1%, 2%, 3%, 4%, 5%, etc.;
[0042] The amount of surfactant used is 0.3-1%, for example 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.;
[0043] The amount of catalyst is 0.3-1.5%, for example, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.;
[0044] The dosage of long-lasting aging-resistant aerogel is 0.1-0.5%, for example, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5% and the like.
[0045] In some specific embodiments, the foaming agent can be selected from physical foaming agents, chemical foaming agents, etc. commonly used in the art, including but not limited to water, monochlorodifluoromethane, monochloromonofluoromethane, dichlorodifluoromethane, trichlorofluoromethane, butane, pentane, cyclopentane, hexane, cyclohexane, heptane, air, CO2 and N2, preferably water.
[0046] Examples of the flame retardant include, but are not limited to, halogenated phosphate flame retardants, phosphate flame retardants, halogenated hydrocarbons and other halogen-containing flame retardants, melamine and its salts, reactive flame retardants, inorganic flame retardants, etc. Such flame retardants can be used alone or in combination. Preferably, the flame retardant is selected from liquid flame retardants with a viscosity of 40 to 800 mPa.s at 25°C; more preferably, the flame retardant has a viscosity of 60 to 400 mPa.s at 25°C; and more preferably, the flame retardant is composed of reactive flame retardants and non-reactive flame retardants. The reactive flame retardant refers to a flame retardant that can participate in the reaction, so that the polyurethane molecules obtained by the reaction have a flame retardant function and have little effect on the material properties. Examples of the reactive flame retardant include but are not limited to tris(dipropylene glycol)phosphite, N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester, N,N-bis(2-hydroxyethyl)aminomethylphosphonic acid dimethyl ester, FR212 (produced by Wanhua Chemical Company), etc. The non-reactive flame retardant refers to a type of flame retardant that can play a flame retardant effect but does not participate in the reaction. Examples of the non-reactive flame retardant include but are not limited to tris(2-chloroethyl)phosphate, (2-chloropropyl)phosphate, di(3-bromo-2,2-dimethylpropyl)phosphate, dimethyl methylphosphate, diethyl ethylphosphate, dimethyl propylphosphate, triethyl phosphate, triphenyl phosphate, tricresyl phosphate, etc. The flame retardant of the present invention enables the polyurethane composition to have a good flame retardant effect, and at the same time has a lower viscosity at room temperature, thereby improving the moldability of the polyurethane composition and the reinforcing material.
[0047] The chain extender can be a commonly used chain extender in the art, such as diols, diamines, diphenols, etc. Examples include but are not limited to ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, butanediol, cyclohexanediol, methylamine, ethylamine, hydrogenated bisphenol A, hydroquinone, etc. Such chain extenders can be used alone or in combination.
[0048] The cross-linking agent can be a commonly used cross-linking agent in the art, such as polyols, polyamines, etc. Examples include but are not limited to trimethylolpropane, glycerol, pentaerythritol, diethanolamine, triethanolamine, ethylenediamine, phenylenediamine, sorbitol, etc. Such cross-linking agents can be used alone or in combination.
[0049] Examples of the surfactant include, but are not limited to, a polysiloxane-oxyalkylene block copolymer as the main structure, and the like. Such surfactants can be used alone or in combination.
[0050] The catalyst refers to a class of compounds that have catalytic activity towards isocyanate and active hydrogen atoms, examples of which include but are not limited to amine catalysts, organometallic catalysts, etc. Such catalysts can be used alone or in combination.
[0051] In some specific embodiments, the isocyanate reactive component may also contain other commonly used additives in the art, including but not limited to coupling agents, color pastes, fillers, smoke suppressants, dyes, pigments, antistatic agents, diluents, surface wetting agents, leveling agents, thixotropic agents, viscosity reducers, plasticizers, etc., which can be understood by those skilled in the art.
[0052] Another key of the present invention is the long-lasting aging-resistant aerogel, which is added to the polyurethane composition for the preparation of polyurethane foam. The long-lasting aging-resistant aerogel replaces the currently commercially available antioxidants and light stabilizers, such as 1135, 2-(2'-hydroxy-5'-benzyl)benzotriazole, etc. The long-lasting aging-resistant aerogel is prepared from calcium carbonate aerogel and a composite anti-aging agent. The polyurethane composition containing the long-lasting aging-resistant aerogel has very good storage stability and process convenience. When preparing polyurethane foam, the foaming efficiency and stability during the foaming process can be improved, and the slow-release effect of antioxidants and light stabilizers in the foam can also be achieved, thereby providing very excellent long-lasting heat-resistant oxygen aging and light-resistant aging performance, and greatly reducing the amount of antioxidants and light stabilizers, significantly reducing the cost of raw materials and construction and maintenance costs, so that the polyurethane curing roadbed technology can achieve economical and reliable large-scale mass production.
[0053] In another aspect of the present invention, a method for preparing polyurethane foam using the aforementioned polyurethane composition comprises the following steps:
[0054] 1) at 10-60° C., respectively, mixing and stirring the isocyanate component and the isocyanate reactive component;
[0055] 2) at 10-60° C., the isocyanate component and the isocyanate reactive component are mixed uniformly by a device and then injected into a mold for reaction, and after the reaction is completed, the mold is opened to obtain a polyurethane foam.
[0056] In a specific embodiment, the mold temperature of step 2) is 10-60°C, for example, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, etc., and the holding time is 50-90 minutes, for example, 50, 60, 70, 80, 90 minutes, etc.
[0057] In another aspect of the present invention, the polyurethane composition or the polyurethane foam prepared by the method is used as a polyurethane foaming molding and curing ballast.
[0058] The specific components involved in the polyurethane composition of the present invention, such as polyols, additives, etc., can be used alone or in combination unless otherwise specified. In addition, the raw materials, processes, methods, parameters, etc. required for the preparation of each component, the parts not described or recorded can refer to the commonly used technology in the field, and will not affect the implementation of the present invention, such as the preparation of polyether polyols, the preparation of catalysts, etc.
[0059] The "hydroxyl value" in the present invention, unless otherwise specified, refers to the average hydroxyl value of the component.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] 1) The present invention provides a long-lasting aging-resistant aerogel and a polyurethane composition containing the aerogel. The polyurethane composition can be used for the preparation of polyurethane foam, especially the preparation of polyurethane foam for cured roadbed, and has low cost, convenient process, excellent mechanical properties and very excellent long-term resistance to heat and oxygen aging and light aging.
[0062] 2) The long-lasting aging-resistant aerogel of the present invention is used in a polyurethane composition, has very good storage stability and process convenience, can improve the foaming efficiency and stability during the foaming process, and can also achieve the sustained release effect of antioxidants and light stabilizers in the foam, thereby providing very excellent long-term resistance to heat and oxygen aging and light aging, and greatly reducing the amount of antioxidants and light stabilizers, significantly reducing the cost of raw materials and construction and maintenance costs, so that the polyurethane cured roadbed technology can achieve economical and reliable large-scale mass production. DETAILED DESCRIPTION
[0063] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.
[0064] The raw materials used in the embodiments and comparative examples are as follows:
[0065] Isocyanate component 1, WANNATE 8605, NCO content 17.1wt%, viscosity 800mPa·s at 25°C, Wanhua Chemical;
[0066] Isocyanate component 2, WANNATE 8609, NCO content 19.8wt%, viscosity 330mPa·s at 25°C, Wanhua Chemical;
[0067] Isocyanate component 3, NCO content 18.6%wt%, prepared from 63% by mass of 4,4-diphenylmethane diisocyanate, 10% of polyoxypropylene and oxyethylene copolymer polyol with a number average molecular weight of 4800, and 27% of polytetrahydrofuran diol with a number average molecular weight of 1000;
[0068] Polyether polyol 1-1, trimethylolpropane-initiated, propylene oxide polymerized, ethylene oxide terminal block added, ethylene oxide content 25wt%, hydroxyl value 20mgKOH / g;
[0069] Polyether polyol 1-2, glycerol initiator, propylene oxide polymerization, ethylene oxide terminal block addition, ethylene oxide content 15wt%, hydroxyl value 28mgKOH / g;
[0070] Polyether polyol 1-3, glycerol initiator, propylene oxide polymerization, ethylene oxide terminal block addition, ethylene oxide content 10wt%, hydroxyl value 40mgKOH / g;
[0071] Polyether polyol 2-1, diethylene glycol starting, propylene oxide and ethylene oxide random copolymerization, ethylene oxide content 10wt%, hydroxyl value 20mgKOH / g;
[0072] Polyether polyol 2-2, starting with ethylene glycol, random copolymerization of propylene oxide and ethylene oxide, ethylene oxide content 5wt%, hydroxyl value 40mgKOH / g;
[0073] Polyether polyol 2-3, starting with propylene glycol, random copolymerization of propylene oxide and ethylene oxide, ethylene oxide content 8wt%, hydroxyl value 35mgKOH / g;
[0074] Polymer polyol 1-1, glycerol-based, hydroxyl value 20 mgKOH / g, solid content 25 wt%;
[0075] Polymer polyol 1-2, trimethylolpropane starting material, hydroxyl value 40 mgKOH / g, solid content 30 wt%;
[0076] Polymer polyol 1-3, glycerol-based, hydroxyl value 28 mgKOH / g, solid content 45 wt%;
[0077] Polyether polyol 3, trimethylolpropane-initiated, propylene oxide polymerization, ethylene oxide terminal block addition, ethylene oxide content 35wt%, hydroxyl value 56mgKOH / g;
[0078] Polyether polyol 4, starting with ethylene glycol, random copolymerization of propylene oxide and ethylene oxide, ethylene oxide content 15wt%, hydroxyl value 84mgKOH / g;
[0079] Polyether polyol 5, a polyoxypropylene and oxyethylene copolymer polyol having a number average molecular weight of 4800;
[0080] Polyether polyol 6, polytetrahydrofuran diol having a number average molecular weight of 1000;
[0081] Polyether polyol 7, polytetrahydrofuran diol having a number average molecular weight of 2000;
[0082] Polyether polyol 8, castor oil and its derivative polyols;
[0083] Foaming agent, water;
[0084] Flame retardant 1, FR212, Wanhua Chemical;
[0085] Flame retardant 2, A710, Hemu New Materials;
[0086] Flame retardant 3, expanded graphite, rock sea carbon material;
[0087] Chain extender 1, ethylene glycol;
[0088] Chain extender 2,1,4-butanediol;
[0089] Cross-linker 1, glycerol;
[0090] Cross-linker 2, diethanolamine;
[0091] Surfactant, WANALYST BM029, Wanhua Chemical;
[0092] Catalyst 1, WANALYST KC141, Wanhua Chemical;
[0093] Catalyst 2, WANALYST KC177, Wanhua Chemical;
[0094] Catalyst 3, triethylenediamine solution (solution concentration is 33%);
[0095] Catalyst 4, dibutyltin dilaurate;
[0096] Antioxidant 1, Chinox 35, Double Bond Company;
[0097] Antioxidant 2, Chinox 168, Double Bond Company;
[0098] Light stabilizer 1, Lowlite 28, Chemtura Corporation;
[0099] Light stabilizer 2, Lowlite 55, Chemtura Corporation.
[0100] Preparation method of long-lasting aging-resistant aerogel 1:
[0101] 50g of calcium oxide was suspended in 1000g of anhydrous methanol and heated to 40°C. After stirring for 90 minutes, carbon dioxide was bubbled through the reaction vessel at a flow rate of 1L / min for 1 hour. When all the calcium oxide was dissolved and converted into alcohol gel, the carbon dioxide was stopped and allowed to stand for 0.5 hours. 20g of the above-mentioned product alcohol gel by weight was placed in an autoclave, and a mixed solution of 3g3,5-di-tert-butyl-4-hydroxyphenylpropionic acid isooctyl ester and 2g2-(2'-hydroxy-3'-dodecyl-5'-methylphenyl)benzotriazole and 5g of anhydrous methanol was added until the gel was just completely immersed in the solution. The autoclave was then sealed and slowly pressurized to 6.0MPa with carbon dioxide at a temperature of 290K. Maintain for 4h, reduce the pressure to 4.0MPa, and then re-pressurize to 6.2MPa with carbon dioxide. Repeat the procedure 3 times. Subsequently, the autoclave was heated to 316K, which is higher than the critical temperature of carbon dioxide, and maintained for 3 hours. After slowly reducing the pressure to atmospheric pressure, a long-lasting aging-resistant aerogel 1 was obtained.
[0102] Preparation method of long-lasting aging-resistant aerogel 2:
[0103] 60g of calcium oxide was suspended in 800g of anhydrous methanol and heated to 50°C. After stirring for 120 minutes, carbon dioxide was bubbled through the reaction vessel at a flow rate of 2L / min for 2 hours. When all the calcium oxide was dissolved and converted into alcohol gel, the carbon dioxide was stopped and allowed to stand for 1 hour. 30g of the above product alcohol gel was placed in an autoclave, and a mixed solution of 7g of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid branched C7-C9 carbon alkyl ester and 3g of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and 10g of anhydrous methanol was added until the gel was just completely immersed in the solution. The autoclave was then sealed and slowly pressurized to 6.2MPa with carbon dioxide at a temperature of 281K. Maintain for 6h, reduce the pressure to 4.5MPa, and then re-pressurize to 6.5MPa with carbon dioxide. Repeat this procedure 4 times. Subsequently, the autoclave was heated to 316K, which is higher than the critical temperature of carbon dioxide, and maintained for 3 hours. After slowly reducing the pressure to atmospheric pressure, a long-lasting aging-resistant aerogel 2 was obtained.
[0104] Preparation method of long-lasting aging-resistant aerogel 3:
[0105] 48g of calcium oxide was suspended in 800g of anhydrous methanol and heated to 45°C. After stirring for 100 minutes, carbon dioxide was bubbled through the reaction vessel at a flow rate of 1.5L / min for 1.5 hours. When all the calcium oxide was dissolved and converted into an alcohol gel, the carbon dioxide was stopped and allowed to stand for 0.8 hours. 30g of the above-mentioned product alcohol gel was placed in an autoclave, and a mixed solution of 6.5g of PUR70, 3.5g of 3-[3-(2H-benzotriazolyl-2)-5-tert-butyl-4-hydroxyphenyl]malonate and polyethylene oxide reaction product and 10g of anhydrous methanol was added until the gel was just completely immersed in the solution. The autoclave was then sealed and slowly pressurized to 6.5MPa with carbon dioxide at a temperature of 292K. Maintain for 5h, reduce the pressure to 4.3MPa, and then re-pressurize to 6.0MPa with carbon dioxide. Repeat this procedure 5 times. Subsequently, the autoclave was heated to 316K, which is higher than the critical temperature of carbon dioxide, and maintained for 3 hours. After slowly reducing the pressure to atmospheric pressure, a long-lasting aging-resistant aerogel 3 was obtained.
[0106] Embodiment, comparative example polyurethane molded foam preparation method:
[0107] 1) at 30° C., respectively, mixing and stirring the isocyanate component and the isocyanate reactive component;
[0108] 2) At 30° C., the isocyanate component and the isocyanate reactive component are mixed uniformly by a device and then injected into a mold for reaction. After the reaction is completed, the mold is opened to obtain a polyurethane foam. The injection pressure is 130 bar, the pouring amount per second is 300 g, the mold temperature is 50° C., and the pressure holding time is 60 minutes.
[0109] The raw materials used in the examples and comparative examples are listed in Table 1.
[0110] Table 1 Raw material data table used in Examples and Comparative Examples (parts by mass)
[0111]
[0112]
[0113] The isocyanate components and isocyanate reactive components of the examples and comparative examples were tested for storage stability using the following test standards and methods:
[0114] The liquid uniformity of the components was measured by static storage at 25°C. The storage stability was determined by the time when the non-uniform liquid began to appear. If the time was less than 7 days, the storage stability was very poor; if the time was between 7 and 21 days, the storage stability was relatively poor; if the time was between 21 and 60 days, the storage stability was relatively good; if the time was greater than 60 days, the compatibility of the two components was very good.
[0115] The polyurethane molded foam samples obtained in the examples and comparative examples were tested using the following test standards and methods:
[0116] (1) Foam density, GB / T 6343;
[0117] (2) Tensile strength and elongation at break, GB / T 6344;
[0118] (3) Tear strength, GB / T 10808
[0119] (4) 10% compressive strength, GB / T 10807;
[0120] (5) Compression set, GB / T 6669;
[0121] (6) Dry heat aging resistance, GB / T 9640, 110℃ for 90 days;
[0122] (7) Resistance to moisture and heat aging, GB / T 9640, 80℃ 95% RH 30 days;
[0123] (8) UV aging resistance, GB / T 16422, 30 days;
[0124] (9) Resistance to low temperature aging, -20℃ for 30 days.
[0125] Items (6) to (9) are all performed after the corresponding standard aging treatment, placed at 20°C for 4 hours, and then tested to calculate the retention rate by comparing the initial performance.
[0126] The storage stability test results of the isocyanate component and the isocyanate reactive component are listed in Table 2.
[0127] Table 2 Test results of the storage stability of the components of the examples and comparative examples at 25°C (isocyanate reactive components)
[0128]
[0129] Table 3 Test results of the storage stability of the components of the embodiments and comparative examples at 25°C (isocyanate component)
[0130]
[0131] The test results of the polyurethane molded foam in its initial state and after aging are listed in Tables 4 to 8 below.
[0132] Table 4 Test results of initial state of polyurethane molded foam of embodiments and comparative examples
[0133]
[0134] Table 5 Example and Comparative Example Polyurethane Molded Foam Dry Heat Aging Resistance Test Results (Retention Rate)
[0135]
[0136] Table 6 Example and Comparative Example Polyurethane Molded Foam Moisture Heat Aging Resistance Test Results (Retention Rate)
[0137]
[0138] Table 7 UV aging resistance test results of polyurethane molded foam of embodiment and comparative example (retention rate)
[0139]
[0140] Table 8 Example and Comparative Example Polyurethane Molded Foam Low Temperature Aging Resistance Test Results (Retention Rate)
[0141]
[0142] It can be seen from Tables 2 and 3 that the examples have significantly better storage stability. The examples can all maintain a uniform liquid state for more than 180 days, while the isocyanate reactive components of Comparative Examples 1 to 3 affect the storage stability due to the addition of a higher number of antioxidants and light stabilizers, and the isocyanate reactive components and isocyanate components of Comparative Example 4 quickly undergo graphite precipitation and component crystallization and solidification. Therefore, for the preparation of the cured roadbed, the examples have the advantage of obvious process convenience; and the high number of antioxidants and light stabilizers in Comparative Examples 1 to 3 will bring higher costs, and Comparative Example 4 requires a continuous heat source at the beginning of the preparation work, which also increases the cost.
[0143] It can be seen from Table 4 that the initial mechanical properties of Comparative Examples 1 to 3 are generally low, which is due to the composition of the isocyanate reactive components. One important reason is that the addition of a higher proportion of antioxidants and light stabilizers leads to a decrease in the mechanical properties of the PU foam body.
[0144] It can be seen from Tables 5 to 8 that the examples have significantly better comprehensive aging resistance. One of the key factors is the use of long-lasting aging-resistant aerogel, which achieves the slow release effect of antioxidants and light stabilizers in the foam, thereby providing very excellent long-lasting aging resistance. The study found that although comparative examples 1 to 3 have used a large number of antioxidants and light stabilizers, the surface performance has also significantly decreased after long-term aging, affecting the overall performance. Comparative example 4 has the worst comprehensive aging resistance because it does not contain aging-resistant raw materials.
[0145] It can be seen from the above embodiments that the comprehensive aging resistance of polyurethane foam can be greatly improved when the long-lasting aging-resistant aerogel of the present invention is used in an amount of less than 0.5wt%. Combined with its advantages of low cost and convenient process, the polyurethane cured roadbed can be economically and reliably mass-produced.
[0146] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A long-lasting aging-resistant aerogel, characterized in that: The invention is prepared from calcium carbonate aerogel and composite anti-aging agent.
2. The long-lasting aging-resistant aerogel according to claim 1, characterized in that: The composite anti-aging agent is composed of an antioxidant and a light stabilizer; Preferably, the composite anti-aging agent is composed of 60-70wt% antioxidant and 30-40wt% light stabilizer; more preferably, the antioxidant is selected from one or more of 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid isooctyl ester, 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid branched C7-C9 carbon alkyl ester, PUR70, PU68F; and / or The light stabilizer is selected from one or more of 2-(2'-hydroxy-3'-dodecyl-5'-methylphenyl)benzotriazole, the reaction product of 3-[3-(2H-benzotriazolyl-2)-5-tert-butyl-4-hydroxyphenyl]malonate and polyethylene oxide, and bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate.
3. The method for preparing the long-lasting aging-resistant aerogel according to claim 1 or 2, characterized in that: The following steps are involved: 1) suspending calcium oxide in anhydrous methanol, heating and stirring, bubbling carbon dioxide through a reactor until all the calcium oxide is dissolved and converted into an alcohol gel, stopping the introduction of carbon dioxide, and allowing the reaction to stand to obtain an alcohol gel; 2) placing the alcohol gel in an autoclave, and adding an anhydrous methanol solution of a composite anti-aging agent until the gel is just completely immersed in the solution; 3) Seal the autoclave, slowly pressurize it with carbon dioxide to no less than 6.0 MPa, control the temperature in the autoclave to 281-292 K, maintain for 4-6 hours, then reduce the pressure to 4.0-4.5 MPa, and then pressurize it with carbon dioxide to no less than 6.0 MPa; 4) Repeat step 3) 3 to 5 times; then, heat the autoclave to a temperature higher than the critical temperature of carbon dioxide, preferably greater than or equal to 316K, and maintain for 1 to 3 hours; 5) Slowly reducing the pressure to atmospheric pressure to obtain the long-lasting aging-resistant aerogel.
4. The preparation method according to claim 3, characterized in that: The heating and stirring in step 1) has a heating and stirring temperature of 40-50° C., a time of 90-120 min, a carbon dioxide flow rate of 1-2 L / min, a bubbling time of 1-2 h, and a standing time of 0.5-1 h; and / or The weight ratio of the composite anti-aging agent to anhydrous methanol in step 2) is 1:1 to 1:1.
5.
5. A polyurethane composition obtained by reacting an isocyanate component and an isocyanate-reactive component, characterized in that: The isocyanate reactive components include: polyether polyol 1, polyether polyol 2, polymer polyol, foaming agent, flame retardant, chain extender, crosslinking agent, surfactant, catalyst, and long-lasting aging-resistant aerogel; Wherein, the long-lasting aging-resistant aerogel is the long-lasting aging-resistant aerogel described in claim 1 or 2 or the long-lasting aging-resistant aerogel prepared by the preparation method described in claim 3 or 4.
6. The polyurethane composition according to claim 5, characterized in that The polyether polyol 1 has an average functionality of 2 to 4.5, preferably 3, a hydroxyl value of 10 to 200 mgKOH / g, preferably 20 to 40 mgKOH / g, and is obtained by reacting ethylene oxide and propylene oxide, and has an ethylene oxide content of 10 to 25 wt%, based on the total mass of propylene oxide and ethylene oxide being 100%; and / or The polyether polyol 2 has an average functionality of 2 to 3, preferably 2, a hydroxyl value of 10 to 200 mgKOH / g, preferably 20 to 40 mgKOH / g, and is obtained by reacting ethylene oxide and propylene oxide, and has an ethylene oxide content of 5 to 10 wt%, based on the total mass of propylene oxide and ethylene oxide being 100%; and / or The polymer polyol, namely the graft copolymer polyether polyol, has an average functionality of 2 to 4.5, preferably 3, a hydroxyl value of 15 to 50 mgKOH / g, preferably 20 to 40 mgKOH / g, and a solid content of 20 to 50 wt%, preferably 25 to 45 wt%.
7. The polyurethane composition according to claim 5, characterized in that The NCO content of the isocyanate component is 10-32%, preferably 17-20%, and the viscosity at 25°C is 100-1000 mPa·s, preferably 300-800 mPa·s; Preferably, the molar ratio of isocyanate groups in the isocyanate component to active hydrogen atoms in the isocyanate reactive component is 80-120:100, preferably 95-105:
100.
8. The polyurethane composition according to any one of claims 5 to 7, characterized in that Based on the total mass of the isocyanate-reactive component, the isocyanate-reactive component comprises:
9. A method for preparing polyurethane foam using the polyurethane composition according to any one of claims 5 to 8, characterized in that: The following steps are included: 1) at 10-60° C., respectively, mixing and stirring the isocyanate component and the isocyanate reactive component for standby use; 2) at 10-60° C., the isocyanate component and the isocyanate reactive component are mixed uniformly by a device and then injected into a mold for reaction, and after the reaction is completed, the mold is opened to obtain a polyurethane foam; Preferably, the mold temperature in step 2) is 10-60° C., and the holding time is 50-90 minutes.
10. Use of the polyurethane composition according to any one of claims 5 to 8 or the polyurethane foam prepared by the method according to claim 9 as a polyurethane foaming molding and curing ballast.
Citation Information
Patent Citations
Polyurethane soft foam material for curing ballast bed and preparation method thereof
CN105237699A
Polyurethane flexible foam material for railway curing ballast bed and preparation method thereof
CN112920377A